The Role of Inclusive Talent Development in Talent Management and Human Resource Sustainability in Consulting Firms - Zulmi, Muhamad Nijar; Prananda , Yulian Rizki (Universitas Muhammadiyah Pontianak, 2026)
This study examines the role of inclusive talent development in strengthening talent management systems and HR sustainability in a consulting firm. Using a qualitative case study approach, data were collected through interviews and document analysis. The results show that equitable training access, internship programs, and skill-matching enhance commitment, retention, and create a sustainable talent pipeline. These findings highlight the importance of inclusive talent development as an organizational strategy to respond to external challenges and support long-term human resource sustainability.